A seamless handover scheme for vehicles across heterogeneous networks. (1st January 2012) - Prakash, A.; Verma, R.; Tripathi, R.; Naik, K.
Next generation heterogeneous networks require an effective handover scheme, optimised specially to support network mobility. The paper proposes an architecture to support seamless mobility of mobile networks across heterogeneous networks. We consider the vehicular scenario where a vehicle is provided with mobility through different internet service providers (ISPs) and propose to use multiple mobile routers-based handover scheme in vehicles. The multiple mobile routers architecture is extended to include multiple home agents (HAs) where each HA belongs to different administrative domains. We carry out comparative performance evaluation of the handover performance of the proposed scheme in regard to UDP and TCP throughput, service disruption time, and signalling overhead. Moreover, we analyse the impact of vehicle speed and overlapping distance of access routers on packet loss during handover period. The simulation results show that the proposed scheme provides a mobile network with seamless mobility across heterogeneous networks. The overlapped reception of packets from different access routers significantly minimises packet losses during handover even without reducing handover latency.